Activation of NMDA receptors mediated iron accumulation via modulating iron transporters in Parkinson's disease. Issue 11 (13th June 2018) - Xu, Huamin; Liu, Xiaodong; Xia, Jianjian; Yu, Tianshu; Qu, Yanan; Jiang, Hong; Xie, Junxia
ABSTRACT: Increasing evidence has confirmed that nigral iron accumulation and activation of NMDA receptors (NRs) contribute to the neurodegeneration of dopamine (DA) neurons in Parkinson's disease (PD). Earlier work indicated that activation of NRs participated in iron metabolism in the hippocampus. However, the relationship between activation of NRs and iron accumulation in DA neurons of the substantia nigra in PD was unknown. In this study, our results showed that NRs inhibitors MK‐801 and AP5 protected nigrostriatal projection system and reduced nigral iron levels of 6‐hydroxydopamine (6‐OHDA)‐induced PD rats. In vitro studies demonstrated that NMDA treatment increased the expression of iron importer divalent metal transporter 1 (DMT1) and decreased the expression of iron exporter ferro‐ potin 1 (Fpn1), which were dependent on iron regulatory protein 1 (IRP1). This led to increased intracellular iron levels and intensified the decrease in mitochondrial transmembrane potential in MES23.5 dopaminergic neurons. In addition, we reported that MK801 and neuronal nitric oxide synthase inhibitor could antagonize 6‐OHDA‐induced up‐ regulation of IRP1 and DMT1 and down‐regulation of Fpn1, thus attenuating 6‐OHDA‐induced iron accumulation in MES23.5 cells. This suggested that 6‐OHDA‐induced activation of NRs might modulate the expression of DMT1 and Fpn1 via the neuronal nitric oxide synthase‐IRP1 pathway.—Xu, H., Liu, X., Xia, J., Yu, T., Qu, Y., Jiang, H., Xie, J., Activation of NMDA receptors mediated iron accumulation via modulating iron transporters in Parkinson's disease. FASEB J. 32, 6100–6111 (2018). www.fasebj.org